2-Methylquinoline promoted oxidative ring-opening of N-sulfonyl aziridines with DMSO: facile synthesis of α-amino aryl ketones. Issue 49 (8th December 2016) - Zhang, Xianhui; Li, Shuai-Shuai; Wang, Liang; Xu, Lubin; Xiao, Jian; Liu, Zhen-Jiang
Abstract: 2-Methylquinoline promoted room-temperature oxidative ring-opening of N -sulfonyl aziridines with DMSO has been developed, providing a mild and convenient method for the synthesis of a variety of different N -sulfonyl protected α-amino aryl ketones. The employment of 2-methylquinoline was crucial for the success of this mild transformation and good to excellent yields could be achieved. Graphical abstract: 2-Methylquinoline promoted room-temperature oxidative ring-opening of N -sulfonyl aziridines with DMSO has been developed, providing a mild and convenient method for the synthesis of a variety of different N -sulfonyl protected α-amino aryl ketones. The employment of 2-methylquinoline was crucial for the success of this mild transformation and good to excellent yields could be achieved.